2019
DOI: 10.1002/wer.1243
|View full text |Cite
|
Sign up to set email alerts
|

Organic micropollutants in groundwater of India—A review

Abstract: Groundwater pollution due to organic micropollutants is a major cause of concern, especially in parts of the world where available water resources are on the decline. India is the largest user of groundwater where the presence of micropollutants in the subsurface environment has been the focus of many researchers. The objective of this study was to provide a detailed review of studies on micropollutants in Indian groundwater and to provide strategies for further work. It is found that the presence of pharmaceu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 58 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…When contaminant degradation or removal processes are not appropriate, these substances are released into water bodies in high amounts due to an enrichment and accumulation effect [3][4][5][6]. After release from WWTPs to water systems, contaminants can bioaccumulate in aquatic species [7][8][9] and be transported to different water bodies (groundwater, river water, lakes) where risk exists to reach water for human consumption (tap water, bottled water) [2,[10][11][12][13]. 2) Industrial, urban, and rural activities release contaminants in waste landfills and liquid discharge lines (3 and 4).…”
Section: Global Problem Of Contaminants In Watermentioning
confidence: 99%
“…When contaminant degradation or removal processes are not appropriate, these substances are released into water bodies in high amounts due to an enrichment and accumulation effect [3][4][5][6]. After release from WWTPs to water systems, contaminants can bioaccumulate in aquatic species [7][8][9] and be transported to different water bodies (groundwater, river water, lakes) where risk exists to reach water for human consumption (tap water, bottled water) [2,[10][11][12][13]. 2) Industrial, urban, and rural activities release contaminants in waste landfills and liquid discharge lines (3 and 4).…”
Section: Global Problem Of Contaminants In Watermentioning
confidence: 99%
“…The Asian country that by far published more studies on the occurrence of pesticides in groundwater is India. Sackaria and Elango (2020) published a review of articles reporting pesticides residues in groundwater from 1995 to 2019. In the tables compiled by Sackaria and Elango (2020), 31 pesticides (16 classified as organochlorine, 11 as organophosphate and 4 as pyrethroids) were referred as detected in this period, reported in 38 research papers.…”
Section: Pesticides In Groundwater In Asiamentioning
confidence: 99%
“…However, a recent study carried out by the Ministry of Agriculture and Farmers’ Welfare which entailed the analysis of 23,660 samples of food commodities concluded that 19.1% of the tested food samples contained pesticide residues and 2.2% of such samples contained pesticides above the prescribed threshold of maximum residues (Food Safety and Standards Authority of India (FSSAI), 2019). In addition to food crops, a substantial degree of evidence indicating the presence of chemical pesticides in groundwater exists for the Indian context (Sackaria & Elango, 2020; Somashekar et al, 2015). Thus, although the aggregate and per hectare use of agricultural pesticides is apparently trivial for India vis-à-vis other countries, challenges associated with direct pesticide exposure and indirect exposure via pesticide residues call for immediate corrective measures.…”
Section: Introductionmentioning
confidence: 99%